Suppression of long intergenic non-protein coding RNA 1123 constrains lower extremity deep vein thrombosis via microRNA-125a-3p to target interleukin 1 receptor type 1. Issue 5 (2nd May 2022) - Yang, Baocai; Zhang, ZiXiang
ABSTRACT: Lower extremity deep vein thrombosis (LEDVT) is a disorder of venous return caused by abnormal blood clotting. LEDVT can obstruct the lumen and is the third most common vascular disease after cerebrovascular disease and coronary artery disease. LncRNAs are associated with thrombosis and potentially affect the pathogenesis of DVT. However, no studies have reported the effect of LINC01123 on LEDVT. The aim of this study was to investigate the effect of LINC01123 on LEDVT in rats via the miR-125a-3p/interleukin 1 receptor type 1 (IL1R1) axis. Lentiviral vectors that altering LINC01123, miR-125a-3p and IL1R1 expression were pre-injected into the tail vein of rats, and an LEDVT model was established 1 day later. Detection of LINC01123, miR-125a-3p and IL1R1 expression was performed. Inflammatory factors in femoral venous blood, the length and weight of the thrombus, the histomorphological changes were determined in the rat model. The targeting relation of miR-125a-3p with LINC01123 or IL1R1 was verified. The results presented that LEDVT rats expressed high LINC01123 and IL1R1 and low miR-125a-3p expression levels. After silencing LINC01123 or elevating miR-125a-3p, the rate of thrombosis, length and weight of thrombus, and levels of inflammatory factors were reduced. The targeting relation was presented between miR-125a-3p with LINC01123 or IL1R1. Elevating IL1R1 was available to turn around the action of silence of LINC01123 on LEDVT rats. All in all, suppression of LINC01123 restrains LEDVT via miR-125a-3p to target IL1R1. Graphical abstract: uf0001